Vietnam Vanguard : the 5th Battalion's Approach to Counter-Insurgency, 1966 - Boxall, Ron; O'Neill, Robert (ANU Press, 2020)
"The Vietnam War, and Australia's part in it, was a major military event, calling for willingness to face death and destruction on the battlefield on the part of those sent there, especially the men of our infantry battalions who formed the spearhead of our forces in Vietnam. For many reasons, the Australian public know relatively little about what our Army did in Vietnam during the war, particularly during the years of our peak commitment, 1965-72. This book attempts to make the true nature of the war clearer to readers, emphasising how hard fought it was during major operations. Twenty-seven of the contributing authors of this book were involved in the 1966 deployment of the 1st Australian Task Force into Phuoc Tuy Province. This formation was the first Australian Army force larger than an infantry battalion group to be deployed into a major war since World War II. 5th Battalion, the Royal Australian Regiment (5 RAR), was in the vanguard as the task force's first element committed to operations to seize and occupy Nui Dat base and embark on establishing dominance over the enemy. The narratives presented in this book give rare insights into thoughts of the soldiers at the time and how they have come to view the Australian Government's hurried expansion of its initial commitment to that war, the Army's state of preparedness for that wider involvement, and how those in its forefront adapted to get the job done, both in and out of operations, despite numerous shortcomings in higher level planning. Both professional soldiers and conscripted national servicemen have contributed viewpoints to these pages."